MERCEDES-MODELLEN: Feltarbejde blandt de u-eksotiske - Knudsen, Anne (Tidsskriftet Antropologi, 1995)
Anne Knudsen: The Mercedes Method The author points to the faet that anthropological field studies generally concem themselves with people of lower social status than that of the ethnographer. Taking as her point of departure a yet-unpublished field study among weli-to-do people in south-westem Europe, she draws attention to the places and methods for encountering members of the upper classes and gives a range of advice as to how one goes about building confidence among sources who do not themselves regard their groups as fit objects for anthropological research. Marcel Mauss’ notions of reciprocity and status are invoked as a guideline for behaviour, and the author claims that the seat next to the driver of a private car is an optimal position for extracting information.